2006
DOI: 10.1073/pnas.0510077103
|View full text |Cite
|
Sign up to set email alerts
|

Controlling methicillin-resistant Staphylococcus aureus : Quantifying the effects of interventions and rapid diagnostic testing

Abstract: Control of nosocomial transmission of methicillin-resistant Staphylococcus aureus (MRSA) has been unsuccessful in most countries. Yet, some countries have maintained low endemic levels by implementing nationwide MRSA-specific infection control measures, such as ''search & destroy'' (S&D). These strategies, however, are not based on well designed studies, and their use in countries with high levels of endemicity is controversial. We present a stochastic three-hospital model and an analytical one-hospital model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
225
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(240 citation statements)
references
References 34 publications
8
225
4
3
Order By: Relevance
“…In jeder dritten Probe der 126 untersuchten Masthähnchen konnten LA-MRSA ST398 in deutlicher Quantität (100-1000 KbE pro ml Auftauwasser) nachgewiesen werden [237]; eine hohe Nachweisrate ist auch für Putenfleisch bekannt [238]. Obwohl LA-MRSA bei allen lebensmittelliefernden Tieren und deren Fleischprodukten nachgewiesen wur- [272,273]. Trotz der umfangreichen Evidenz, die für die Implementation von MRSA-Screenings spricht, haben einige Studien keine Effektivität dieser Maßnahme dokumentieren können [274][275][276][277][278] In einer aktuellen Studie aus Melbourne [295] (ITS, 4.194 Aufnahmen, MRSA-Prävalenz 5,7 %) stieg das Risiko einer MRSA-Infektion mit der Zahl der kolonisierten Abstrichorte (HR, 3,4 bei mehr als einem positiven Abstrichort; 95 %-CI 1,2-9,9).…”
Section: Kastenunclassified
“…In jeder dritten Probe der 126 untersuchten Masthähnchen konnten LA-MRSA ST398 in deutlicher Quantität (100-1000 KbE pro ml Auftauwasser) nachgewiesen werden [237]; eine hohe Nachweisrate ist auch für Putenfleisch bekannt [238]. Obwohl LA-MRSA bei allen lebensmittelliefernden Tieren und deren Fleischprodukten nachgewiesen wur- [272,273]. Trotz der umfangreichen Evidenz, die für die Implementation von MRSA-Screenings spricht, haben einige Studien keine Effektivität dieser Maßnahme dokumentieren können [274][275][276][277][278] In einer aktuellen Studie aus Melbourne [295] (ITS, 4.194 Aufnahmen, MRSA-Prävalenz 5,7 %) stieg das Risiko einer MRSA-Infektion mit der Zahl der kolonisierten Abstrichorte (HR, 3,4 bei mehr als einem positiven Abstrichort; 95 %-CI 1,2-9,9).…”
Section: Kastenunclassified
“…To summarize, MRSA harboring genetic markers of CA-MRSA have increased over the past years at our hospital and appear to replace traditional hospital MRSA strains. Bootsma et al [26] already predicted in their model that CA-MRSA strains would replace, not add to, traditional HA-MRSA strains. Data from our study and those by Popovich support this model [22].…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase (ESBL)-producing Escherichia coli are two of the commonest MDR pathogens at present causing worldwide concern. 1,2 It is reported that 69.8% of all S. aureus isolates are resistant to oxacillin, 3 while ESBL-producing E. coli accounts for 11% of all E. coli isolates in Hong Kong. 4 Antimicrobial photodynamic inactivation (PDI) is perhaps an alternative strategy to combat these MDR pathogens.…”
Section: Introductionmentioning
confidence: 99%